The Effect Of Islamic Values, Entrepreneurial Mindset, And Self-Efficacy On Students’ Interest In Entrepreneurship: Pengaruh Nilai Islami ,Mindeset Kewirausahaan, Dan Efikasi Diri terhadap Minat Berwirausaha Mahasiswa - Pasaribu, Sri Pujiyama; Nawawi, Zuhrinal M; Atika, Atika (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Indonesia faces a 4.91% unemployment rate in 2024, with university graduates contributing significantly due to limited entrepreneurial skills. Specific Background: At FEBI UINSU, only 30% of students show interest in entrepreneurship despite the integration of Islamic values in the curriculum. Knowledge Gap: Previous studies predominantly examine two variables, leaving limited understanding of the combined relationship among Islamic values, entrepreneurial mindset, and self-efficacy. Aims: This study analyzes the partial and simultaneous relationships of Islamic values, entrepreneurial mindset, and self-efficacy with entrepreneurial interest among FEBI UINSU students. Results: The findings show that 85% of entrepreneurial interest is explained by the three variables. Islamic values and entrepreneurial mindset demonstrate negative and non-significant relationships, while self-efficacy shows a positive and significant relationship. Simultaneous testing confirms that all variables collectively relate significantly to entrepreneurial interest (F count 178.388 > F table 3.095; sig 0.001). Novelty: This study introduces an integrated three-variable model combining spiritual, cognitive, and psychological dimensions within Islamic entrepreneurship. Implications: The results provide theoretical enrichment for Islamic entrepreneurship literature and offer data-driven recommendations for curriculum development in FEBI UINSU. Highlights• Self-belief demonstrates the strongest statistical association with student business intention• Ethical-religious and cognitive factors show non-significant statistical relationships individually• Combined model explains 85% variance of entrepreneurial intention KeywordsIslamic Values; Entrepreneurial Mindset; Self Efficacy; Entrepreneurial Interest; Islamic Entrepreneurship